Interest rate pass-through in Germany and the euro area - Julia von Borstel (Research On Money in the Economy (ROME), 2008)
This paper analyzes the interest rate pass-through for Germany and the euro area using for the first time a fully harmonized data set on bank retail rates. In a vector error correction model, the speed and completeness of the pass-through from market rates to bank interest rates are estimated for the period January 2003 to September 2007. We find that time deposit and corporate loan rates other than overdrafts adapt relatively fast to changes in refinancing costs, followed by rates for private housing loans. On the contrary, especially longer term consumer lending rates and rates for savings deposits show the most sluggish pass-through behavior. In contrast to earlier studies, results for Germany and the euro area excluding Germany are similar by and large. We therefore conclude that differences in the pass-through behavior seem to be associated rather with certain banking products than with cross-country differences.
Keywords: E43; G21; C32; 330; Monetary policy transmission; interest rate channel; vector error correction model